SAT0504 The association of myositis specific antibodies in patients with inflammatory myositis: preliminary data in indian patients. (12th June 2018) - Negalur, N.V.; Raval, D.; Bindroo, M.; Kazi, W.; Baveja, U.; Gupta, R.
Abstract : Background: Studies in Autoimmune Inflammatory Myositis (AIM) have shown that certain antibodies have a role in the diagnosis and prognosis of patients with myositis. This ongoing study presents the preliminary data of 48 patients of Indian AIM. Objectives: To study the prevalence of Myositis specific and Myositis Associated antibodies (MSA and MAA respectively) in Indian patients with AIM and to correlate these antibodies with clinical features. Methods: All consecutive patients with Inflammatory myositis (satisfying the Bohan and Peter criteria, 1975 attending the Rheumatology and Clinical Immunology department of Medanta hospital from November 2016 to October 2017 were included prospectively and divided into groups as Dermatomyositis (DM), Polymyositis (PM), CTD associated myositis (CTD-M), Cancer associated myositis (CAM) and Juvenile Myositis (JM). Their clinical data and sera were collected after obtaining informed consent. Sera was analysed for IgG antibodies against Jo-1, PL-7, PL-12, EJ, SRP, Mi-2, MDA-5, TIF1γ, SAE1, SAE2, NXP2 and SSA/R052kD using the microELISA technique (BlueDriver Dot Myositis 12 SAE IgG kit). Their ENA was also recorded (Blue DriverQuantrix-ANA25 Screen IgG kit d-tek). Results were read by the BlueScan scanner and value ≥10 were considered positive. The study was approved by the Ethics committee of Medanta hospital. Results: There were 48 patients in the cohort (M:F=12:36) with the mean age of 41.3 years and a median disease duration of 30 months. Nineteen of them were DM, 19 were PM, 5 were CTD-M, 2 were CAM and 3 were JM. 58.3% were ANA positive and MSA were positive in 37.5% of the cohort, MSA being mutually exclusive. Antibodies against Mi-2 were present in 6 patients (12.5%), Jo-1 antibodies in 5 (10.4%), 2 (4.1%) patients each had PL-7 and SRP antibodies. One patient (2%) each had MDA-5, NXP2 and TIf1γ antibodies. MAAs were seen in 39.5% of the cohort with antibodies against Ro, RNP and PM- Scl seen in 16 (33.3%), 2 (4.1%) and 1 (2%) respectively. Mi-2 antibodies were seen only in DM and JM group. The lone patient who had MDA-5 antibody had amyopathic DM. Malignancy screening was negative in NXP2 and TIF1γ antibody positive patients. Conclusions: MSA were present in almost 40% of the cohort. Mi-2 antibodies were associated with rash and none had ILD whereas Jo-1 antibodies were associated with mechanic hands, arthritis and ILD. With further recruitment of patients in this ongoing study, we hope to get more robust data in future. Disclosure of Interest: None declared